PENGARUH PERPUTARAN KAS DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PT. MITRA ADIPERKASA STORE NEW ERA DI MEDAN - Nugroho, Radhityo; Rangkuti, Sahnan; Zahri, Cut (Bisnis-Net, 2025)
Cash and inventory turnover reflect whether a company's operations are running smoothly or not, ultimately affecting its ability to generate profits. The faster a company's cash and inventory turnover, the more likely it is to increase its profits. This study aims to determine the effect of cash and inventory turnover on profitability at PT. Mitra Adiperkasa Store New Era in Medan. This study uses cash and inventory turnover as independent variables and profitability as the dependent variable.This study is a quantitative study using financial statement data for the 2019-2023 period. Sampling was conducted using a saturated sampling technique. Data processing was carried out using descriptive statistics and classical tests (normality, multicollinearity, heteroscedasticity, and autocorrelation). Furthermore, multiple linear regression analysis (T-test, F-test, and determination test) was conducted using SPSS version 25.The results of this study indicate that, based on the t-test, cash and inventory turnover have a partial positive and significant effect on profitability. Meanwhile, the F-test results suggest that both cash and inventory turnover have a positive and significant impact on company profitability simultaneously. Furthermore, the determination test results indicate that cash turnover and control variables can influence profitability by 62.1%, with the remaining 37.9% influencing other variables not yet examined.Furthermore, the discussion reveals a decline in cash turnover related to suboptimal inventory management, with the increase in cash exceeding the increase in sales. Moreover, the company's inventory turnover slowed, and inventory was held in the warehouse for relatively long periods, resulting in declining sales and profitability levels, as well as failure to meet company targets, and inefficient management costs.